Bio-inspired fault-tolerant algorithms for network-on-chip - Sethi, Muhammad Athar Javed (New York, NY : CRC Press/Taylor & Francis Group, 2020)
"Network on Chip (NoC) addresses the communication requirement of different nodes on System on Chip. The bio-inspired algorithms improve the bandwidth utilization, maximize the throughput and reduce the end-to-end latency and inter-flit arrival time. This book exclusively presents in-depth information regarding bio-inspired algorithms solving real world problems focusing on fault-tolerant algorithms inspired by the biological brain and implemented on NoC. It further documents the bio-inspired algorithms in general and more specifically, in the design of NoC. It gives an exhaustive review and analysis of the NoC architectures developed during the last decade according to various parameters"--
OCLC-licensed vendor bibliographic record.
Keywords: Networks on a chip -- Mathematics; Fault-tolerant computing; Biomimicry; COMPUTERS / Computer Engineering; TECHNOLOGY / Electronics / Circuits / General; TECHNOLOGY / Electronics / Microelectronics